Re-Evaluation of Nicotinic Acetylcholine Receptors in Rat Brain by a Tissue-Segment Binding Assay - Wang, Mao H.; Yoshiki, Hatsumi; Anisuzzaman, Abu Syed M.; Uwada, Junsuke; Nishimune, Atsushi; Lee, Kung S.; Taniguchi, Takanobu; Muramatsu, Ikunobu (Frontiers in Pharmacology, 2011)
Nicotinic acetylcholine receptors (nAChRs) of cerebral cortex and cerebellum of rats were evaluated by a radioligand binding assay, employing tissue segments or homogenates as materials. [3H]-epibatidine specifically bound to nAChRs in rat cortex or cerebellum, but the dissociation constants for [3H]-epibatidine differed between segments and homogenates (187 and 42 pM in cortex, and 160 and 84 pM in cerebellum, respectively). The abundance of total nAChRs was approximately 310 and 170 fmol/mg protein in the segments of cortex and cerebellum, respectively, which were significantly higher than those (115 and 76 fmol/mg protein) estimated in the homogenates of cortex and cerebellum. Most of [3H]-epibatidine binding sites in the cortex segments (approximately 70 % in population) showed high affinity for nicotine, dihydro--erythroidine or cytisine, but the binding sites in cerebellum segments were mostly low affinity for nicotine. An upregulation of nAChRs by chronic administration of nicotine was observed in the cortex segments but was not in the cerebellum segments with [3H]-epibatidine as a ligand. The upregulation in the cortex was caused by a specific increase in high affinity sites for nicotine. The present study shows that tissue integrity is important for a precise quantitative as well as qualitative estimation of nAChRs in rat brain. Nicotine-induced upregulation was caused by a specific increase in high affinity sites for nicotine (probably 42) of cerebral cortex.